Monetary policy uncertainty: A tale of two tails - Tatjana Dahlhaus; Tatevik Sekhposyan (Bank of Canada, 2018)
We document a strong asymmetry in the evolution of federal funds rate expectations and map this observed asymmetry into measures of monetary policy uncertainty. We show that periods of monetary policy tightening and easing are distinctly related to downside (policy rate is higher than expected) and upside (policy rate is lower than expected) uncertainty. Downside monetary policy uncertainty decreases over time, while upside uncertainty remains rather stable, reflecting the asymmetry in the behavior of the expectational errors - a finding that we attribute to changes in the conduct of monetary policy. We show that this behavior cannot be entirely explained by uncertainty in macroeconomic fundamentals: the asymmetry remains even when we control for macroeconomic uncertainty, emphasizing the importance of monetary policy implementation. Finally, we assess the macroeconomic effects of monetary policy uncertainty. We find that the effects are non-linear and conditional on the economy being in an easing or tightening regime. Though uncertainty is, in general, recessionary, its effects are stronger in a monetary easing regime relative to a tightening one.
Keywords: C18; C32; E02; E43; E52; 330; Transmission of monetary policy; Monetary policy communications; Econometric and statistical methods; Business fluctuations and cycles; Uncertainty and monetary policy